The development of the visual culture of design students in shaping the spatial environment - M. Maiorova, Irina (2019)
The article presents the results of a study devoted to the development of students – designers’ visual culture of shaping the subject - spatial environment.Visual culture is considered as a combination of means of artistic - design expressiveness and visual experience, influencing the nature of the shaping of the subject - spatial environment. The development of visual culture will be effective if it is understood as a culture of aesthetic interaction of a person with visual artistic images and consists of three interrelated links: the perception of visual information, the expression of personal evaluation, the creation of expressive visual images.To diagnose the development of visual culture, we have proposed an interpretation method. In the methodological literature, it is treated as a solution to the problem in an unexpected way - in a different style, in a strange manner, “working in a masked wizard” - “if Le Corbusier had done the same project.” Based on the proposed assignment, the purpose of which was to study various stylistic and plastic techniques in the creative activities of famous designers - to create an image of the interior in the style of the master.As a result of a comparative analysis of diagnostics of the null and control stage of the creative work of the experimental group, we obtained quantitative and qualitative data that comprehensively characterize the level of development of the visual culture of students according to the selected criteria: readiness for design - communication, readiness for perception and analysis, interpretation ability, ability of reflection. The reliability of the evaluation of the results obtained was determined using mathematical and static data processing.